Subjects of intergenerational justice: indigenous philosophy, the environment and relationships - Winter, Christine J. (Routledge environmental humanities, 2022)
Chapter 1 Introduction Section 1: Framings Chapter 2: Liberal Approaches to Intergenerational Environmental Justice Chapter 3: The Settler State, Recognition and Power Section 2: Living at the Intersection: Barriers to realising IEJ in settler states Chapter 4: Still Talking Past Each Other: More than homo economicus Chapter 5: You are Never Alone -- something more than individual Chapter 6: Growing the Land Up: Listening to Country Section 3 How do we relate? Chapter 7: Walking Backwards into the Future: Something more than now Chapter 8: Regenerative Relationships